ANALISIS PELAKSANAAN PEMASARAN PADA PT. RIAUJAYA CEMERLANG II AHMAD YANI (KASUS BENGKEL RESMI SEPEDA MOTOR MEREK SUZUKI AHMAD YANI PEKANBARU) - Putra, Rahmadani; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The problem in this study is the decline in revenue service motorcyclePT. Ahmad Yani Riaujaya II Shining in the last five years, the lack of marketingefforts undertaken and the high prices of my services and spare parts whencompared to general workshops. The purpose of the study was to assess andanalyze the implementation of marketing at PT. Riaujaya Shining II Ahmad Yani(Case Official Workshop Suzuki Motorcycles Ahmad Yani Pekanbaru). Thecollection of data through questionnaires to 97 people who come to serve theirbikes in the PT. Riaujaya Shining II Ahmad Yani. Respondents to theimplementation of marketing at PT. Riaujaya Shining II Ahmad Yani (CaseOfficial Workshop Suzuki Motorcycles Ahmad Yani Pekanbaru) assessedrespondents had good execution. Implementation of marketing at PT. RiaujayaShining II Ahmad Yani which includes indicators of product, price, promotion,location, people, process and physical evidence. Indicator of product, location,people and processes considered to be very good, the price is good enoughindicator, the indicators are not good and the promotion assessed for indicators ofphysical evidence is considered to be good.Kata Kunci : product, price, promotion, place, people, process, physical evidence